Evaluasi Dan Analisis Peruntukan Lahan Hutan Kota Menggunakan Citra Landsat 8 Dan Sistem Informasi Geografis Di Kota Magelang - MANAN, Abdul ([Yogyakarta] : Universitas Gadjah Mada, 2014)
An urban environmental problems which occurred these day becoming more complex, especially environment degradation due to the reducing of green open spaces in urban areas such as urban forest. Urban forest is one of the green open spaces in urban area which can be used for reducing air pollution level and also used for recreation area. According to PP No. 63 year 2002 the spacious percentage of urban forest is 10% in minimum compare to total urban area. Citra Landsat 8 and GIS can help to find an available potential land area and obtain for the development of urban forest, so urban forest can be develop into 10% of the total urban area. The purpose of this study is to identify the large and determine the distribution of urban forest in Magelang city. Whether it is in accordance with PP No. 63 Year 2002 or not, and if it was not, then the analysis on urban forest land use to achieve 10% large of the total urban area in Magelang is needed. The basic method of this study was a survey method with remote sensing approach. This method was used to get the data from research location with the instrument. These instrument was satellite remote sensing Landsat 8 and the spatial data analysis using ArcGIS software. The image of urban forest on Landsat 8 imagery was the area with more than 11 pixels on 15 x 15 meter size which connected each other. Interpretation result showed the total collection trees were 189.10 ha. There were 41.47 Ha in North Magelang district and 112.94 Ha in South Magelang district. Collection trees showed as urban forest was on Tidar hill. Other land can be used to develop as potential urban forest. There were three priority categories on developing urban forest, main priority 27.38 Ha or 1.47%, second priority 151.14 Ha or 8.13% and third priority 44.31 Ha or 2.38% from the total area of Magelang city.